2002
DOI: 10.1002/ddr.10073
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies of Alzheimer's disease through manipulation of Aβ metabolism: a focus on Aβ‐degrading peptidase, neprilysin

Abstract: Deposition of amyloid-b peptide (Ab), a pathological hallmark of Alzheimer's disease (AD), locates upstream of the AD cascade. Ab is constantly anabolized and catabolized in the brain, and the steady-state Ab level is physiologically determined by the metabolic balance between the anabolic and catabolic activities. Even subtle alterations in this metabolic balance over a long period of time could turn Ab into a pathogenic agent that influences both the pathological progression and incidence of the disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…172,173 However, the use of metal chelators as possible drugs to reduce the Ab burden can be hindered by the fact that many Ab degrading metalloproteases require zinc for their activity. 174 For this reason, metal protein attenuating compounds (MPACs) like clioquinol (CQ) and derivatives, initially designed to control metal dyshomeostasis, have been recently reviewed for alternative mechanisms related to their potential ability to promote Ab clearance via PI3-K/Akt activation and MMPs up-regulation. It has been demonstrated that CQ modulates secreted levels of Ab in vitro promoting intracellular increase of copper and zinc and acting as an ionophore agent.…”
Section: Metal Ions Signaling Affecting Proteolytic Enzymes Activitymentioning
confidence: 99%
“…172,173 However, the use of metal chelators as possible drugs to reduce the Ab burden can be hindered by the fact that many Ab degrading metalloproteases require zinc for their activity. 174 For this reason, metal protein attenuating compounds (MPACs) like clioquinol (CQ) and derivatives, initially designed to control metal dyshomeostasis, have been recently reviewed for alternative mechanisms related to their potential ability to promote Ab clearance via PI3-K/Akt activation and MMPs up-regulation. It has been demonstrated that CQ modulates secreted levels of Ab in vitro promoting intracellular increase of copper and zinc and acting as an ionophore agent.…”
Section: Metal Ions Signaling Affecting Proteolytic Enzymes Activitymentioning
confidence: 99%